Towards a Critical Construction Management Research Agenda in the MENA Region - Abu-Salah, Alaa' (2014)
A Master of Science thesis in Civil Engineering by Alaa' Abu-Salah entitled, "Towards a Critical Construction Management Research Agenda in the MENA Region," submitted in March 2014. Thesis advisor is Dr. Sameh M. El-Sayegh. Available are both soft and hard copies of the thesis.